2016
DOI: 10.5194/amt-9-1685-2016
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability of temperature in the UTLS region over Ganges–Brahmaputra–Meghna river basin based on COSMIC GNSS RO data

Abstract: Abstract. Poor reliability of radiosonde records across South Asia imposes serious challenges in understanding the structure of upper-tropospheric and lower-stratospheric (UTLS) region. The Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) mission launched in April 2006 has overcome many observational limitations inherent in conventional atmospheric sounding instruments. This study examines the interannual variability of UTLS temperature over the Ganges-Brahmaputra-Meghna (GBM) r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Over tropical Asia (−0.54 (±0.04) K decade −1 ) temperatures show a tendency to decrease, but without significance at the 95 % level. This result is puzzling because it is assumed that the temperature increases in the tropics in the UT, equivalent to the surface temperature (Khandu et al, 2016). One reason could be related to the tropopause definition, but O 3 (40-80 ppb) and PV (always below 1 PVU) indicate that the selected air mass is tropospheric.…”
Section: Temperature Anomalies and Trendsmentioning
confidence: 79%
See 1 more Smart Citation
“…Over tropical Asia (−0.54 (±0.04) K decade −1 ) temperatures show a tendency to decrease, but without significance at the 95 % level. This result is puzzling because it is assumed that the temperature increases in the tropics in the UT, equivalent to the surface temperature (Khandu et al, 2016). One reason could be related to the tropopause definition, but O 3 (40-80 ppb) and PV (always below 1 PVU) indicate that the selected air mass is tropospheric.…”
Section: Temperature Anomalies and Trendsmentioning
confidence: 79%
“…A wellsuited data source for temperature profiles is the relatively new Global Positioning System radio occultation (GPSRO) technique (Kursinski et al, 1997;Wickert et al, 2001). The reliability of these measurements within the UTLS region has been demonstrated with trend analyses of GPSRO temperature (Steiner et al, 2009) or GPSRO-derived trends in the thermal tropopause temperature and tropopause height (Schmidt et al, 2010;Rieckh et al, 2014;Khandu et al, 2016). Ho et al (2017) demonstrated the usefulness of the GPSRO measurements to correct the temperature bias of radiosondes with different sensor types in the lowermost stratosphere (LMS), which is an important task to reduce the temperature uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, GNSS-RO emerges as a valuable tool for monitoring convection processes and obtaining precise measurements of tropopause height and temperature. There have been several studies that have utilized GNSS-RO data to determine tropopause temperature and height at different scales, ranging from global to regional analyses (Awange et al, 2011;Khandu et al, 2016;Nascimento et al, 2020;Schmidt et al, 2005;Schmidt et al, 2008). However, it appears that no specific studies have been conducted for the Vu Gia-Thu Bon river basin using GNSS-RO data.…”
Section: Introductionmentioning
confidence: 99%